# calculus

posted by .

Find the derivative using the chain rule.
f(x) = ((3x-7)/(6x+3))^4
f '(x) =

let u= 3x-7
v= (6x+3)^-4

Then d(uv)= u dv + v du

du= 3 dv= -4(6x+3)^-5 (6)

so what's f'(x)? (thanks for your help)

Goodness. f'(x) is d(uv)

I will be happy to critique your work or thinking.

in the orginal problem, the entire thing is squared to the 4th power not just the denominator. and also, where and how did u change 4 to a -4?

I didn't see that. OK, change u to ((3x-7)^4 that changes du to 12(3x-7)^3

v= 1/(6x+3)^4= (6x+3)^-4

are u sure u change it to 12(3x-7)^3 and not 4(3x-7)^3?? i'm just curious. i'm trying to follow u but my derivative came out different from urs again.

## Similar Questions

1. ### MoRe HeLp PlEaSe!! (calc)

Also can I get some help with this LONG, TIRESOME PROBLEM?
2. ### Math, Calculus

Find the derivative of the function. y= xcosx - sinx What's the derivative?
3. ### Calculus

Find the derivative: h(x)=7x/sqrt(5-2x) Using the chain rule...I figured out my previous post.
4. ### Calculus

How do I use the chain rule to find the derivative of square root(1-x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used?
5. ### Calculus

find the derivative of f(x)=((x^2+3)^5+x)^2 using the chain rule. I know that I would start with f'(x)=2((x^2+3)^5+x) but I don't know how to do the rest
6. ### calculus

Please help. Applying the chain rule, how do I find the derivative of f(x)=In(e^x-e^-x) (x>0) and then using this answer use the quotient rule to find the second derivative. I cannot do this so any answer greatly appreciated.
7. ### calculus-derivatives

y=cos^3(12theta) find derivative using chain rule
8. ### CAlculus

using chain rule find the derivative of y=xsin1/x
9. ### Applied Calculus

Find the derivative of this function: g(t)=(8t+10)^2*(10t^2-7)^-3 Using the Chain Rule.
10. ### Calculus

1.) Find the derivative of tan (sec x). 2.) Find the derivative if 1/x in four ways, using the limit process, power rule, quotient rule and implicit differentiation. 3.) Show that the derivative of sec^-1 x is 1/(|x|*sqrt(x^2 -1)). …

More Similar Questions